Pengaruh variasi campuran bahan bakar pertamax dan bioetanol 99,9% terhadap torsi mesin bensin 4 langkah Tecquipment TD201 - Risano, A. Yudi Eka; Wardono, Herry; Sihombing, Gunawan Poniton R.P. (Universitas Muhammadiyah Metro, 2021)
Bioethanol is ethanol made from plants such as cassava, sugarcane, sago, which are processed through hydrolysis, fermentation, distillation and dehydration processes. Lampung Province is one of the largest producers of cassava in Indonesia, with the total productivity of 5,451,312 tons in 2017, and 6,683,758 tons in 2018 or there was an increase of 22,61% compared to 2017. From this data, it is possible to produce bioethanol, where every 1 kg of cassava can produce 0,106 liters of bioethanol. This is what underlies this research to investigate the effect of blending bioethanol of 99% with pertamax and bioethanol on the engine torque. Blending bioethanol of 99% can homogeusly mix. The engine used in this study is a Kohler gasoline engine equipped with a VDAS (Versatile Data Accession System) instrument unit in determining the parameters of engine performance. The blending of bioethanol of 99% as big as 14% (E14) gave the highest value of torque at 1 rotation of dynamometer valve opening and engine speed of 2000 rpm.